Karakterisasi Tiga Lokus Mikrosatelit pada Telur dan Larva Tuna Sirip Kuning, Thunnus albacares - Moria, Sari B.; Permana, Gusti N.; Hutapea, Jhon H. (Jurnal Perikanan Universitas Gadjah Mada, 2009)
Characterization of three microsatellite loci are able to provide information about genetic variation or polymorphism of yellow fin tuna eggs and larvae produced by domestication of broodstock. Thirty samples of eggs and larvae were collected from different spawning day and analyzed. Amplification of those three loci were carried out with multiflexing technique and electrophoreted ABI Prism 310 Genetic Analyzer sequencer. From those three loci were used (Ttho-1, Ttho-4 and Ttho-7) showed that locus Ttho-7 had higher genetic variance (0.720-1.212) compared to others loci. Based on the result, it can be concluded that high allele frequency as showed at Ttho-7 could be used as marker for  parental analysis.